GENERALIZED α-MIN SPECIAL TYPE CONTRACTION RESULTS ON 2-MENGER SPACES - Bhandari, Samir Kumar; Chandok, Sumit (Bulletin of Natural Sciences Research, 2022)
The goal of this paper is to present some novel probabilistic α-minimum contraction results on probabilistic 2-metric spaces. Our findings are based on probabilistic 2-metric spaces, which are the probabilistic generalisations of 2-metric spaces. An illustrative example backs up our findings.
Keywords: 2-Menger spaces; Cauchy sequence; Fixed point; ϕ-function; Altering distance function